GPT AI in Computer Science Education: A Systematic Mapping Study - Strik, Bruno H.; Menolli, André; Brancher, Jacques Duílio (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.242103, 2024)
With the advent of GPT-AI, new possibilities in education emerged. However, it is challenging to determine how and when to apply these new technologies and understand their actual impact on teaching and learning. This study conducts a systematic mapping to gather, include, and classify scientific papers that investigated the subject of generative AI in CS education. 31 relevant studies that conducted empirical evaluations of the application of GPT-AI tools in CS education were collected. Our findings highlight challenges regarding plagiarism, learning perception, and AI capability. The main contribution of this study is to present research opportunities and provide a background for future studies that address the application of GPT-AI in CS education.